Perspectives of the Primary School Curriculum Rewrite (PCR) Implementation in One Primary School - Beepot, Ritesh Lyndell (My University, 2017)
This study investigated teachers’ and administrators’ perceptions about the implementation of the new primary school curriculum at a school in central Trinidad. Data were collected through interviews with five participants (two administrators and three teachers) and document analysis. The findings revealed that while the PCR was viewed as a novel attempt to modernize the education system, its effectiveness was being impacted by issues of: 1) allocation of time and resources, (2) the physical infrastructure of the school, 3) its inadequacy for implementation, and 4) the heavy workload that attended the implementation process.
Keywords: Case studies; Teacher attitudes; Administrator attitudes; Primary school curriculum; Curriculum implementation; Trinidad and Tobago